Pengembangan e-Modul dengan pendekatan STEAM untuk meningkatkan kemampuan berpikir kreatif matematis siswa - Priyatno, Sigit; Walid, Walid; Cahyono, Nur Adi (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2023)
This research aims to develop learning media for material on the rules of sines and cosines that is valid, effective and gets a positive response from students. The research method used is Research and Development (RD) with a 4-D model with stages 1) Define, 2) Design, 3) Develop, and 4) Disseminate. The learning media developed resulted in a product called "Motrionik" (Modul Trigonometri Elektronik) with a STEAM approach. This research was conducted at SMA Negeri 1 Semarang involving 32 class X students. Data analysis techniques used are qualitative and quantitative data analysis. Qualitative data analysis was carried out through theoretical studies and observations, while quantitative data analysis was carried out by calculating validation scores, tests and student responses. The results show that the electronic module developed is suitable for use based on expert validation in the very appropriate category, is effective in improving learning outcomes based on test results, and gets responses in the very good category based on student response sheets.